The Brain Drain. A Survey of the Literature - Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
This paper reviews the theoretical and empirical literature on Brain Drain (BD). We propose an ideal path that links the first studies with the most recent ones. In this development, the literature on BD focuses on a variety of economic and social issues and recalls to national and international debates. This paper uses more than 350 articles from a variety of sources. The sources are specialized professionals journals, internet research engines, governmental publications and newspapers. In the first part we analyse briefly the BD, its different definitions and the historical roots of the BD. This part shows that the BD is a wide and complex phenomenon. In the second part, we propose an ideal path to interpret the literature. This part analyses how BD is linked to political and social events, according to the Economy.
Keywords: 330; Brain Drain